Answer:
see explanation
Explanation:
Expand the left side and equate to like terms on the right side
(2 - 3i)(x + yi)
= 2x + 2iy - 3ix - 3yi² ← using i² = - 1, then
= 2x + 2iy - 3ix + 3y → compare with 4 + i
2x + 3y = 4 → (1)
- 3x + 2y = 1 → (2)
Multiply (1) by 3 and (2) by 2
6x + 9y = 12 → (3)
- 6x + 4y = 2 → (4)
Add (3) and (4) term by term to eliminate term in x
13y = 14 ( divide both sides by 13 )
y =
![(14)/(13)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/wlhbbbsazj5w9tmcafzbzph5br68scxgz7.png)
Substitute this value into (1) and solve for x
2x +
=
![(52)/(13)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/lbvs81lkb20go9ya7a1jy2el1m08ovjgk9.png)
Subtract
from both sides
2x =
← divide both sides by 2
x =
![(5)/(13)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/xtu1l7ebwpxl9bq7wj3zhz0wcs9dc954fz.png)
Hence x =
and y =
![(14)/(13)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/wlhbbbsazj5w9tmcafzbzph5br68scxgz7.png)